Joint trajectories of disease activity, and physical and mental health-related quality of life in an inception lupus cohort. (19th March 2020) - Fung, William; Lim, Lily Siok Hoon; Tomlinson, George; Engel, Lisa; Su, Jiandong; Diaz-Martinez, Juan Pablo; Touma, Zahi
Abstract: Objectives: To examine for latent patterns of SLE disease activity trajectories that associate with specific latent patterns of health-related quality of life (HRQoL; Medical Outcomes Study Short Form-36), and to determine baseline predictors of class membership. Methods: In this retrospective longitudinal inception cohort of 222 SLE adults over 10 years, trajectories of three outcomes were studied jointly: Short Form-36 physical (PCS) and mental (MCS) component summaries and adjusted mean SLEDAI-2000 (AMS). Group-based joint trajectory modelling was used to model latent classes; univariable and multivariable analyses were used to identify predictors of class membership. Results: Four latent classes were identified: Class 1 (C1) (24%) had moderate AMS, and persistently low PCS and MCS; C2 (26%) had low AMS, moderate PCS and improved then worsened MCS; C3 (38%) had moderate AMS, and persistently high PCS and MCS; and C4 (11%) had high AMS, moderate-low PCS and improving MCS. Baseline older age was associated with lower HRQoL trajectories. Higher AMS trajectories did not associate with a particular pattern of HRQoL trajectory. A higher prevalence of fibromyalgia (44% in C1) was associated with worse HRQoL trajectories. Disease manifestations, organ damage and cumulative glucocorticoid were not differentially distributed across the latent classes. Conclusion: High disease activity did not necessarily associate with low HRQoL. More patients with worse HRQoL trajectories had fibromyalgia. Older age at diagnosis increased the probability of belonging to a class with low HRQoL trajectories. The care of SLE patients may be improved through addressing fibromyalgia in addition to disease activity.